2002
DOI: 10.1046/j.1365-2311.2002.00420.x
|View full text |Cite
|
Sign up to set email alerts
|

Fitness advantage from nuptial gifts in female fireflies

Abstract: 1. In many insects, males provide nuptial gifts to females in the form of spermatophores, sperm‐containing structures produced by male accessory glands. 2. The work reported here examined the influence of both spermatophore number and spermatophore size on female reproductive output in two related firefly beetles, Photinus ignitus and Ellychnia corrusca (Coleoptera: Lampyridae). Based on differences in adult diet, male spermatophores were predicted to increase female reproductive output to a greater extent in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
52
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 23 publications
2
52
0
Order By: Relevance
“…Baker et al , 2001;Drnevich et al , 2001 ) and substances in the ejaculate may induce egg production (see, for example, Chapman et al , 1998 ) and stimulate oviposition ( Leopold, 1976;Eberhard, 1996 ). Therefore, in many studies demonstrating direct benefits from nuptial gifts ( Hayashi, 1998;Ryne et al , 2001;Fedorka & Mousseau, 2002;Rooney & Lewis, 2002 ; for earlier papers see Vahed, 1998 ) it is difficult to disentangle benefits from nuptial feeding from other effects resulting from multiple mating or increased sperm transfer (but see Gwynne, 1984;Steele, 1986;Simmons, 1988Simmons, , 1990Brown, 1997;Reinhold, 1999 ). In this study, using the scorpionfly Panorpa cognata (Ramb.)…”
Section: Introductionmentioning
confidence: 97%
“…Baker et al , 2001;Drnevich et al , 2001 ) and substances in the ejaculate may induce egg production (see, for example, Chapman et al , 1998 ) and stimulate oviposition ( Leopold, 1976;Eberhard, 1996 ). Therefore, in many studies demonstrating direct benefits from nuptial gifts ( Hayashi, 1998;Ryne et al , 2001;Fedorka & Mousseau, 2002;Rooney & Lewis, 2002 ; for earlier papers see Vahed, 1998 ) it is difficult to disentangle benefits from nuptial feeding from other effects resulting from multiple mating or increased sperm transfer (but see Gwynne, 1984;Steele, 1986;Simmons, 1988Simmons, , 1990Brown, 1997;Reinhold, 1999 ). In this study, using the scorpionfly Panorpa cognata (Ramb.)…”
Section: Introductionmentioning
confidence: 97%
“…Because of this, such gifts could potentially alter the allocation strategies used by both sexes (Boggs, 1990(Boggs, , 2009. Previous work in Photinus fireflies (Coleoptera: Lampyridae) has shown that females incorporate proteins derived from male gifts (spermatophores) into their developing oocytes (Rooney and Lewis, 1999), and that such gifts benefit females by increasing their lifetime fecundity (Rooney and Lewis, 2002) and longevity . A phylogenetic study within the Lampyridae recently demonstrated correlated evolution between flightlessness in females and male production of nuptial gifts .…”
Section: Introductionmentioning
confidence: 99%
“…The males of Photinus and Luciola fireflies also provide nutrition to conspecific females during copulation (Rooney and Lewis 1999;Cratsley et al 2003;South et al 2008a;South et al 2008b;South and Lewis 2012). These nuptial gifts contain nutrients essential for egg production in Photinus females (Rooney and Lewis 2002;Cratsley et al 2003;Lewis et al 2004). Photuris fireflies however have a slightly different way of obtaining nutrition.…”
Section: Introductionmentioning
confidence: 99%